(untitled) (Ghana Journal of Science, Technology and Development, 2025)
This study delves into the prevalence of parasitic infestations in domesticated pigs (Sus domesticus) and wild Warthogs (Phacochoerus aethiopicus living in and around the Mole National Park. Fourteen each of domesticated pigs and wild warthogs were selected for fecal sampling and subsequent parasitological analysis. Key parasite load and prevalence rates were assessed using the Floatation Technique and Mc Master Counting Chamber. There was no significant difference (p>0.05) between pigs and warthogs regarding FEC of Strogyle sp, Strongyloides, Trichuris trichuria, Schistosoma mansonii and Taenia sp. However, pigs had significantly higher (p<0.022) average FEC of Nematodirus (1050.0 Â± 429.3 EPG) compared to the warthog which recorded none. Domesticated pigs, Strongyle sp showed the highest prevalence rate of 71.4% while the Trichuris trichuria had the least prevalence rate of 14.3%. However, Ascaris sp, Schistosoma mansonii, and Taenia sp were not detected in domestic pigs. In the wild warthogs group, Strongyle sp had the highest prevalence of 85.7% while Schistosoma mansoni had the least prevalence rate of 14.3%, but Trichuris trichuria was not observed in wild warthogs. The study provides insights into the prevalence of parasitic infestations in wild warthogs and domesticated pigs living in and around the Mole National Park as they live close to each other. The observed differences in prevalence rates highlight the potential influence of ecological factors and host specificity on parasitic dynamics. The study offers valuable insights into the parasitic dynamics of these suids, which can have implications for local wildlife management.